CONTRIBUTION OF CORPORATE SOCIAL RESPONSIBILITY, GOOD CORPORATE GOVERNANCE AND TAX AVOIDANCE TO THE ENERGY SECTOR’S FINANCIAL PERFORMANCE - Kharisma Anandita Sari; Nor Norisanti; Faizal Mulia Z (Proceeding of International Seminar on Agricultural Conservation and Cultural Heritage, 2025)
This study aims to examine the effect of corporate social responsibility, good corporate governance and tax avoidance on the financial performance of energy sector mining companies listed on the Indonesia Stock Exchange. This research uses a quantitative approach with descriptive and associative methods. The sample was selected using purposive sampling technique and 30 observations were obtained based on certain criteria, with the observation period during 2023. Financial performance is measured by profitability ratio proxied by return on equity. The data analysis technique uses multiple linear regression. The results show that corporate social responsibility disclosure and good corporate governance have an effect on financial performance as measured by return on equity, while tax avoidance has no significant effect on financial performance. The implications of these findings suggest that companies need to prioritize CSR as part of their business strategy, as consistent implementation can increase public trust. In addition, constructive oversight through the role of an independent board of commissioners is important to support sustainability-oriented decisions. Although tax avoidance has not been shown to have a significant impact on financial performance, companies are advised to avoid aggressive tax avoidance strategies and focus more on compliance and transparency in financial reporting.